(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
Monitoring and forecasting the technical condition of power equipment is an integral part of technical diagnostics, which is intended to ensure the safety, functional reliability and efficiency of the technical facility, as well as to solve the problems of reducing maintenance costs and reducing the number of downtime losses due to failures [1]. The possibilities of monitoring systems in the energy sector are presented in a number of works (Leyserovich A. Sh., Kumenko A. I., Osika L. K., Chernetsky M. Y., Korshikova A. A. and D. R.). Different approaches to the assessment of the technical condition of energy facilities, prospects for the use of monitoring and diagnostic systems are shown. In this article, the purpose of this article is to analyze the forecasting and monitoring systems of electric power equipment, as well as to test the measured and projected values during the operation of the monitor. At the same time, monitoring and forecasting systems of foreign and domestic manufacturers, methods of creating models of operation of power equipment are presented.